Rekonstrukcija mifopoetičeskogo obraza utki (Anas) (po dannym pis’mennyh istočnikov i fol’klora baltijcev, slavjan i drugih I-E narodov) Reconstruction of the Mythopoetical Image of a Duck (Anas) (According to the Written Sources and Folklore Data of Baltic, Slavic and the Other I-E Peoples) - Kregždys, Rolandas (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article deals with the reconstruction of the mythopoetical image of a duck (Anas) according to the written sources and folklore data of Baltic, Slavic and the other Indo-European peoples. It also presents an etymological analysis of Russ. dial. анчýтка ‘devil, demon; Antichrist; hobgoblin, water-sprite, familiar, sylvan; trollop; poor person; pickle; curse’.